Patient Counting: What Old Records Tell about the Battle for Souls in England and the English Witch Hanging - Slater, Kate (Pomegranate, 2002)
How important is it for us to know the history of the beliefs and customs we weave into Neopaganism? You may be a lore maven or an experience maven or maybe both if you can find the time and energy. For lore mavens here are a couple of plums.